2009
DOI: 10.1152/ajpendo.00235.2009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms involved in Sertoli cell adaptation to glucose deprivation

Abstract: cells provide the physical support and the necessary environment for germ cell development. Among the products secreted by Sertoli cells, lactate, the preferred energy substrate for spermatocytes and spermatids, is present. Considering the essential role of lactate on germ cell metabolism, it is supposed that Sertoli cells must ensure its production even in adverse conditions, such as those that would result from a decrease in glucose levels in the extracellular milieu. The aim of the present study was to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 52 publications
0
51
1
Order By: Relevance
“…In this context, the transport of glucose through the plasma membrane is the rate-limiting step in glucose metabolism and, consequently, in lactate production (Riera et al 2001(Riera et al , 2009. Glucose enters the cell by carrier proteins called glucose transporters (known as GLUTs or SLC2A).…”
Section: Cox and Pgs In Sertoli Cellsmentioning
confidence: 99%
“…In this context, the transport of glucose through the plasma membrane is the rate-limiting step in glucose metabolism and, consequently, in lactate production (Riera et al 2001(Riera et al , 2009. Glucose enters the cell by carrier proteins called glucose transporters (known as GLUTs or SLC2A).…”
Section: Cox and Pgs In Sertoli Cellsmentioning
confidence: 99%
“…is observed even in the complete absence of glucose in a culture medium (33). The less intense but significant expression of MCT1 in spermatocytes and spermatids suggests the sufficient uptake of lactate and other monocarboxylates by MCT1; this is supported by the colocalization of CD147, which is involved in the trafficking of MCT molecules to the cell membrane.…”
Section: Resultsmentioning
confidence: 96%
“…Fresh frozen sections, 14-μm-thick, were fixed with 4% formaldehyde in 0.1 M phosphate buffer for 15 min and then acetylated with 0.25% acetic anhydride in 0.1 M triethanolamine-HCl (pH 8.0) for 10 min. Hybridization was performed at 42°C for 10 h with a hybridization buffer containing 33 P-labeled oligonucleotide probes (10,000 cpm/μL). The sections were rinsed at room temperature for 30 min in 2 × SSC (1 × SSC: 150 mM sodium chloride, 15 mM sodium citrate) containing 0.1% N-lauroylsarcosine sodium, then rinsed twice at 55°C for 40 min in 0.1 × SSC containing 0.1% N-lauroylsarcosine sodium, dehydrated through a graded series of ethanol, and air-dried.…”
mentioning
confidence: 99%
“…Testicular energy metabolism shows some form of specificity in which lactate is the main substrate for energy (ATP) production in germ cells (Oliveira et al, 2012). In vitro studies with cultured Sertoli cells have shown that removing either insulin (Oliveira et al, 2012) or glucose (Riera et al, 2009) from the culture medium results in adaptation of the Sertoli cells to glucose transport as seen in modulated gene expression of glucose transporters (GLUT1 and GLUT3). However, Oliveira et al, (2012) have reported that the insulindeprived Sertoli cells in their in vitro experiment (which closely mimics T1DM) have reduced glucose utilization even when the gene expression of the glucose transporters is increased.…”
Section: Testicular Effects Energy Metabolism In the Testismentioning
confidence: 99%